REKONSTRUKSI SPIRIT HARMONI MELALUI KPM POSDAYA BERBASIS MASJID DI KECAMATAN PULUNG, KABUPATEN PONOROGO - Mukhibat Mukhibat (Harmoni, 2015)
This research was conducted in Pulung Ponorogo to figure out the development model in forming the harmonious spirit of social-religious life through the Thematic Community Service Internship (KPM) Posdaya (Family Empowerment Post)-Mosque Based. First, the thematic Community Service Internship (KPM) Posdaya (Family Empowerment Post)- Mosque Based in STAIN Ponorogo with Participant Action Research (PAR) approach had been able to create spaces and integrative communication medium and decreased the rigidity of communication among different community. Social activities centralized at mosque made people conscious that their religion taught a wisdom to build harmonious life. Second, the difference became positive energy in developing harmony, peacefulness and prosperity. The dialogue activities enriched their theological dialogue empowering mosque in wider perpectives that not only function as praying and preaching but also education, economic, social, culture, communication and information activities.